2019
DOI: 10.1007/s11064-019-02789-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed miRNAs Influence Metabolic Processes in Pituitary Oncocytoma

Abstract: Spindle cell oncocytomas (SCO) of the pituitary are rare tumors accounting for 0.1–0.4% of all sellar tumors. Due to their rarity, little information is available regarding their pathogenesis. Our aim was to investigate miRNA expression profile of pituitary oncocytomas. Total RNA was extracted from 9 formalin-fixed paraffin embedded pituitary samples (4 primary, 3 recurrent oncocytomas and 2 normal tissues). Next-generation sequencing was performed for miRNA profiling. Transcriptome data of additional 6 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, the clinical significance and role of miR‐127‐3p in the osseous metastasis of PCa remains highly unexplored. Previous studies have demonstrated that the dysregulation of miR‐127‐3p is involved in several diseases, such as pituitary oncocytoma, multiple sclerosis, recurrent miscarriage, doxorubicin‐induced cardiotoxicity, frontotemporal dementia, adenovirus‐infected pneumonia, and primary myelofibrosis . For tumors, many studies have indicated that miR‐127‐3p may serve as either a tumor activator or a suppressor depending on the cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical significance and role of miR‐127‐3p in the osseous metastasis of PCa remains highly unexplored. Previous studies have demonstrated that the dysregulation of miR‐127‐3p is involved in several diseases, such as pituitary oncocytoma, multiple sclerosis, recurrent miscarriage, doxorubicin‐induced cardiotoxicity, frontotemporal dementia, adenovirus‐infected pneumonia, and primary myelofibrosis . For tumors, many studies have indicated that miR‐127‐3p may serve as either a tumor activator or a suppressor depending on the cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increase of exosomal hsa-miR-744-5p has been identified in patients with SUDs at the short-term withdrawal stage and it is positively correlated with serotonin concentration in the serum in both HDPs and MDPs (Figure S5). Previous studies have also shown that hsa-miR-744-5p inhibits cell proliferation and invasion in pituitary oncocytoma and epithelial ovarian cancer (Chen et al, 2019a;Krokker et al, 2019;Zhao et al, 2020). Herein, we performed bioinformatical analysis and identified genes PSENEN, FDX1L, VPS37D, SPTBN4, PPP5C, and FAM57B, as potential targets of hsa-miR-744-5p (Figure 4K).…”
Section: Discussionmentioning
confidence: 90%
“…MiRNA expression profiling and NGS data analysis were done as we earlier reported [ 26 , 59 ]. For miRNA sequencing, libraries were prepared using 5 ul RNA and the QIAseq™ miRNA Library Kit (Qiagen, Cat #331505) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%